# Derivación

 TABLA DE DERIVACION y=k y'=0 y=x y'=1 y=xn y'=nxn-1 y=k*f(x) y'=k*f'(x) y=f(x)+g(x) y'=f'(x)+g'(x) y=f(x)*g(x) y'=f'(x)*g(x)+g'(x)*f(x) y=f(x)/g(x) y'=f'(x)g(x)-g'(x)f(x)/g2(x) y=Sen x y'=Cos x y=Cos x y'= -Sen x y=tag x y'=1/Cos2 x y'=1+tag2*x y=Sec x y'=Sec x*tag x y=Cosec x y'= -Cosec x*Cotag x y=Cotag x y'=-1/Sen2 x y'=-1-Cotg2 x y=logax y'=1/x * loga e y=loga f(x) y'=1/f(x) * loga e * f'(x) y=ln x y'= 1/x y=ln f(x) y'= 1/f(x) * f'(x) y=ax y'=ax * ln a y=af(x) y'=af'(x) * ln a * f'(x) y=ex y'=ex y=efx) y'=ef(x) * f'(x) y=arc Sen x y'=1/1-x2 ½ y=arc Sen f(x) y'=1/1-f2(x)1/2(x) * f'(x) y=arcCos x y'= - 1/1-x2 ½ y=arc Cos f(x) y'= -1/1-f2(x)1/2(x) * f'(x) y=arc tag x y'=1/1+x2 y=arc tag f(x) y'=1/1+f2(x) y=arc Cotag x y'= -1/1+x2 y=arc Cotag f(x) y'=1/1+f2(x) * f'(x) y=[f(x)]n y'=n[f(x)]n-1f'(x) y=f(x) 1/n y'=1/n * [f(x)n-1]1/n f'(x)

 TABLA DE DERIVACION y=k y'=0 y=x y'=1 y=xn y'=nxn-1 y=k*f(x) y'=k*f'(x) y=f(x)+g(x) y'=f'(x)+g'(x) y=f(x)*g(x) y'=f'(x)*g(x)+g'(x)*f(x) y=f(x)/g(x) y'=f'(x)g(x)-g'(x)f(x)/g2(x) y=Sen x y'=Cos x y=Cos x y'= -Sen x y=tag x y'=1/Cos2 x y'=1+tag2*x y=Sec x y'=Sec x*tag x y=Cosec x y'= -Cosec x*Cotag x y=Cotag x y'=-1/Sen2 x y'=-1-Cotg2 x y=logax y'=1/x * loga e y=loga f(x) y'=1/f(x) * loga e * f'(x) y=ln x y'= 1/x y=ln f(x) y'= 1/f(x) * f'(x) y=ax y'=ax * ln a y=af(x) y'=af'(x) * ln a * f'(x) y=ex y'=ex y=efx) y'=ef(x) * f'(x) y=arc Sen x y'=1/1-x2 ½ y=arc Sen f(x) y'=1/1-f2(x)1/2(x) * f'(x) y=arcCos x y'= - 1/1-x2 ½ y=arc Cos f(x) y'= -1/1-f2(x)1/2(x) * f'(x) y=arc tag x y'=1/1+x2 y=arc tag f(x) y'=1/1+f2(x) y=arc Cotag x y'= -1/1+x2 y=arc Cotag f(x) y'=1/1+f2(x) * f'(x) y=[f(x)]n y'=n[f(x)]n-1f'(x) y=f(x) 1/n y'=1/n * [f(x)n-1]1/n f'(x)

 Enviado por: Pedro Leira Jiménez Idioma: castellano País: España

Palabras clave:
Te va a interesar